The Campaign To Stop Killer Robots : Legal And Ethical Challenges Posed By Weaponised Artificial Intelligence And Implications For Arms Control Regimes - Henwood, Roland David (University of Pretoria, 2021)
Mini Dissertation (MA (Security Studies))--University of Pretoria, 2021.